KAJIAN INDIKATOR IKLIM USAHA PERDAGANGAN DKI JAKARTA - Bagas Haryotejo; Sefiani Rayadiani (Buletin Ilmiah Litbang Perdagangan, 2009)
Business climate of a country or a region reflect the performance of the concerned Government in control of policies and regulations, both in the landscape and in the operational landscape concept. In general trade business climate in Indonesia had not sufficiently demonstrated a satisfactory condition. Results weighting of trading business climate, namely: (1) the licensing indicators (0,146); (2) security conditions (0,146); (3) conditions of the business environment (0,127); (4) public infrastructure services (0,114); and (5) employment regulation (0,102). While indicators are graded so do not give access to financing is the influence of the company (with the value weights 0,059). Results of the assessment of the business climate in the capital Jakarta with using 10 indicators weighted by pointing out Jakarta, with a value of 3,178 and included into the category quite conducive. The three indicators that contributes is the largest security conditions (3,282), employment (3,191) regulations, and customs (3,175), while the three indicators that have the lowest value is taxation (2,587), land/soil conditions (2,824), and licensing (2,893). Implication of this policy is that business climate improved trade opportunities still can and is very necessary, not least by improving the performance of various indicators mentioned earlier. The very conditions expected from results 'quite conducive' is a two-way communication between the Government in collaboration with entrepreneurs and who are able to establish partnerships in a variety of activities.